Digital Transformation: Challenges And Implementation Electronic Medical Record System In Indonesia - Ni Luh Arum Puspitaning Ati (Lambung Mangkurat University, 2024)
Medical records play a pivotal role in ensuring the delivery of quality healthcare services. However, the fragmented nature of medical record data across different health services leads to redundancy in health administration and implementation challenges. This research aims to delineate the implementation of an electronic medical record (EMR) system in health service agencies and the associated challenges in Indonesia. Employing a literature review method utilizing the Google Scholar database, the study conducted article searches using Indonesian keywords such as